2018
DOI: 10.1039/c7nr08891d
|View full text |Cite
|
Sign up to set email alerts
|

The role of amine ligands in governing film morphology and electrical properties of copper films derived from copper formate-based molecular inks

Abstract: Copper formate complexes with various primary amines, secondary amines and pyridines were prepared, and their decomposition into conductive films was characterized. A comparison of the various complexes reveals that the temperature of thermolysis depends on the number of hydrogen bonds that can be formed between the amine and formate ligands. The particle size resulting from sintering of the copper complexes is shown to depend on the fraction of amine ligand released during the thermolysis reaction. The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 29 publications
9
74
0
Order By: Relevance
“…[85] Following the large interest in Cuf-amine based inks, Paquet et al conducted an extensive study on the role that amine ligands play in determining the properties of the Cu films. [86] Differing from previous studies, they isolated single crystals of their compounds and determined their structures via singlecrystal XRD, in order to present better chemical insight relating structure to decomposition profile. TGA curves of Cuf complexed with various primary and secondary amines suggested that the amines play an important role in lowering the activation energy of the formate decomposition, thereby lowering the decomposition temperature of these complexes (Figure 13).…”
Section: Copper Mod Inksmentioning
confidence: 99%
“…[85] Following the large interest in Cuf-amine based inks, Paquet et al conducted an extensive study on the role that amine ligands play in determining the properties of the Cu films. [86] Differing from previous studies, they isolated single crystals of their compounds and determined their structures via singlecrystal XRD, in order to present better chemical insight relating structure to decomposition profile. TGA curves of Cuf complexed with various primary and secondary amines suggested that the amines play an important role in lowering the activation energy of the formate decomposition, thereby lowering the decomposition temperature of these complexes (Figure 13).…”
Section: Copper Mod Inksmentioning
confidence: 99%
“…Choi et al [10] explained the temperature shift by the electron-donating nature of the coordinating alkylamine, which would facilitate the release of the present carboxylate groups, and reducing properties of hexylamine. Eventually, Paquet et al [22] reported a correlation between hydrogen bond formation properties between the amine and formate groups affecting sterical hindrance and the in-situ reduction temperature. Yet none of these hypotheses have been validated by an in-depth direct investigation of the reduction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…3) and the morphology and the electrical properties of copper films derived from these complex inks. 103 Correlations between the properties of the amines, such as boiling point and coordination strength, with the morphology and electrical performance of the copper films, were established. Highly conductive films could be generated from copper formate inks when the coordinating amine can direct the growth of small particles and form dense films.…”
Section: Solubilization Methodsmentioning
confidence: 99%
“…As described in Section 3, copper or silver particle-free inks have been developed due to their low cost, flexibility in preparation and a relatively low-temperature sintering in comparison with the nano silver or copper-based inks. The ink of copper formate 52,88,92,101,103,108,132,133 or silver oxalate 51,99,106 has made significant development with their advantages over other types of metal inks. This type of ink, however, also has drawbacks.…”
Section: Hybrid Metal Particle-free Inksmentioning
confidence: 99%